P I – 1–9 Health effects of ultrafine particles – a systematic literature review. (18th March 2018) - Kappeler, Ron; Ohlwein, Simone; Tobollik, Myriam; Plaß, Dietrich; Hoffmann, Barbara; Künzli, Nino
Abstract : Background/aim: Evidence from toxicological studies suggests that Ultrafine Particles (UFP) can be inhaled deeply into the lungs and can infiltrate the blood stream. Therefore, UFPs might be more harmful for human health than larger particles. Since the last systematic review, new epidemiological studies were published. Thus, we aimed for an updated review of studies evaluating the health effects of UFPs. Methods: We systematically searched in MEDLINE and the LUDOK database applying two search strategies identifying relevant epidemiological studies published after the HEI-review from 2013 until May 2017. We considered quantitative health effects of environmentally related UFPs (with at least one of the following measurements: UFP particle mass <100 nm, Quasi-UFP particle mass <250 nm, particle number concentration <100 nm, Nucleation mode, Accumulation-mode, Aitken-mode and/or surface area concentration). Studies investigating effects of industrially generated nanoparticles or particles emitted in workplace settings, as well as toxicological and controlled exposure studies were excluded. No limitations were set concerning the health endpoints. Only German and English articles were included. Results: We identified 80 epidemiological studies for our review, including 29 panel, 13 time-series, 9 crossover, 8 cross-sectional, 7 cohort, 6 case-crossover, 4 scripted exposure, and 2 case-control studies. Two studies were not classified according to our categories. Most studies (73) had a short-term study design. The analyses are ongoing and the results will be presented at the conference. Conclusion: The variety and number of studies identified through our literature review poses the need to systematically reassess the health effects of UFPs. Consequently, there is also the need to assess the study quality to further appraise the harmful effects of UFPs.